Effects of agricultural gypsum with micronutrients on the yield and quality of bread wheat - Félix-Fuentes, José Luis; Gutiérrez-Coronado, Marco Antonio (Revista Mexicana de Ciencias Agrícolas, 2025)
Wheat is a crop that requires large amounts of fertilizer; nevertheless, its availability limits productivity. In alkaline soils, nutrients such as iron (Fe), copper (Cu), zinc (Zn) and manganese (Mn) are less available, which causes deficiencies that are reflected in the yield and quality of the grain. Faced with this problem, a study was conducted during the 2023-2024 autumn-winter agricultural cycle at the Norman E. Borlaug Experimental Field, located in the Yaqui Valley. Five treatments with different doses of agricultural gypsum (25 and 50 kg ha-1) enriched with micronutrients (Fe, Cu, Zn, and Mn), with and without humic and fulvic acids, were evaluated to determine the effect of the optimal dose that contributes to improving the yield and quality of Borlaug 100 bread wheat. The experimental design consisted of randomized complete blocks with four replications. The variables evaluated included: soil pH at different depths, nutrient analysis of the flag leaf, yield components, and quality parameters (protein, sedimentation index, incidence of white belly, and partial bunt). The results showed that the treatments with the high dose of agricultural gypsum and micronutrients led to a temporary acidification of the soil until the stem elongation stage, no longer than 30 days, due to a cation exchange, generating an acid hydrolysis that releases hydrogen ions, which indirectly contributed to acidification, which suggests a greater availability of nutrients for the development of the crop. This resulted in a 17% increase in yield in treatments 1 and 3 compared to the control, with a 14% increase in the number of grains per spike. In addition, values of 11.6% of protein were obtained, with less than 0.5% incidence of white belly.
Keywords: fulvic acids; humic acids; micronutrients